Community Enterprises - Aliens under Attack - Bruno S. Frey; Roger Lüthi; Margit Osterloh (Center for Research in Economics, Management and the Arts (CREMA), 2011)
Management research has long focused on for-profit organizations that produce privately owned resources based on central authority and within well-defined boundaries. In recent times, a new kind of enterprise has emerged that we call Community Enterprises. They are private sector not for profit organizations that produce innovation resources and make them freely available to follow-on creators. Starting in the software industry, Community Enterprises have become leading providers of fundamental building blocks for innovation. They create enormous economic value by producing generative technologies that everyone can use and improve. However, this value is hardly measurable. Most importantly, Community Enterprises collide with the appropriation strategies of firms, which aim at acquiring exclusive control of useful resources. They are a major competitive force to for-profit firms and therefore are under attack. We analyze Community Enterprises as aliens in the market economy to which they provide essential resources. We find that market regulation cannot ensure their activities. Instead, we argue that the easiest way to do so is to support Community Enterprises through terms and conditions on government procurement and funding.
Keywords: 330